Alternative casting technologies at the gas-tuibine complex “Zorja” -“Mashinproject” - G. F. Mjalnitsa; L. A. Gilmutdinov; A. I. Chmyr (Литьë и металлургия)
There are given the results of computer modeling of the process of the foundry details production, the analysis of efficiency of working of the foundry modeling system, carried out comparison of the results of the theoretical and experimental investigations.